Ketahanan Budaya di Maluku sebagai Pendekatan Pendidikan Identitas Lokal dalam Meredam Potensi Konflik - Khakim, Muhammad Salisul; Faidati, Nur; Askuri, Askuri (Jurnal Ketahanan Nasional, 2025)
ABSTRACTThe article aims to provide solutions to reduce the potential for conflict in Maluku through a local identity education approach as cultural resilience. This research seeks to find opportunities for local governments in preserving the local identity of the Maluku people through the conservation of the names of Maluku people.The research method uses a qualitative approach with descriptive explanation. Data collection techniques in this study were conducted by using purposive sampling technique. Data collection was carried out primarily through in-depth interviews, and supplemented with secondary data from scientific journals, books and online news, including from government websites. The name data is then analyzed by coding based on language or words which are then classified into several categories. This study uses data analysis techniques through data reduction, presentation, and verification. The results of this study indicate that the names of Maluku people are local identities that play an important role in building national identity. This research is expected to be of concern to academics, other researchers, and the government in assessing policies and managing potential conflicts. The government can approach the cultural conservation of the names of people typical of the Moluccas through local identity education as a nationally integrated